Optical potential-well array for high-selectivity, massive trapping and sorting at nanoscale - Shi, Yuzhi (2021)
Optical tweezers are versatile tools capable of sorting microparticles, yet formidable challenges are present in the separation of nanoparticles smaller than 200 nm. The difficulties arise from the controversy on the requirement of a tightly focused light spot in order to create strong optical forces while a large area is kept for the sorting. To overcome this problem, we create a near-field potential well array with connected tiny hotspots in a large scale. This situation can sort nanoparticles with sizes from 100 to 500 nm, based on the differentiated energy depths of each potential well. In this way, nanoparticles of 200, 300, and 500 nm can be selectively trapped in this microchannel by appropriately tuning the laser power. Our approach provides a robust and unprecedented recipe for optical trapping and separation of nanoparticles and biomolecules, such that it presents a huge potential in the physical and biomedical sciences.